A review on novel non‐thermal food processing techniques for mycotoxin reduction. (13th August 2020) - Adebo, Oluwafemi Ayodeji; Molelekoa, Tumisi; Makhuvele, Rhulani; Adebiyi, Janet Adeyinka; Oyedeji, Ajibola Bamikole; Gbashi, Sefater; Adefisoye, Martins Ajibade; Ogundele, Opeoluwa Mayowa; Njobeh, Patrick Berka
Abstract: The overarching challenges of mycotoxin contamination in food necessitate the development of strategies to be implemented to combat their effects thereof. Common processing techniques have been utilised but do not necessarily meet the desired efficacy. This review appraises studies on novel non‐thermal food processing techniques, particularly high pressure processing, pulsed electric filed, cold plasma and ultrasound processing for the decontamination of mycotoxins in food. Although available studies on these techniques have suggested a reduction of mycotoxins and in some instances, complete decontamination of mycotoxins was also reported. The mechanisms by which reduction/elimination occurs include through decomposition of toxins after collision with ions/electrons leading to cleavage of bonds, structural degradation of the mycotoxins structure and cleavage of functional groups. Additional studies into the toxicity of degraded products and the composition of the food products are still required to ensure a more widespread adoption of these techniques to enhance food safety. Abstract : Mycotoxin reduction through novel thermal techniques